Program Evaluation of Pancasila Student Profile Strengthening Project Using the CSE-UCLA Model - Devi Kurniawati, Agatha Ratna; Iriani, Ade; Satyawati, Sophia Tri (Jurnal Paedagogy, 2024)
The research aims to evaluate the program of the Pancasila student profile strengthening project in elementary schools in Semarang Regency, Indonesia. This research method used the CSE-UCLA evaluation model with a qualitative approach that included the aspects of program assessment, program planning, program implementation, program improvement, and program certification. The data sources came from the school principal/curriculum teachers, classroom teachers, students, and the parents of students at Pangudi Luhur Ambarawa Elementary School and Tlompakan 1 Tuntang Elementary School in Semarang Regency. Data collection was through interviews, document studies, and observations. The data analysis technique used qualitative descriptive methods. The research results showed that in the Assessment program, P5 was implemented in accordance with the vision, mission, and objectives. The theme and project options were chosen based on environmental issues and the needs of the students, and the project was also supported by the parents; Program planning, both schools had goals to be achieved in P5 so that the project ran with a clear direction and purpose; Program implementation, teachers have good strategies in carrying out P5 but improvements were needed in the socialization of the P5 program; Program improvement, there needs to be enhancements in the documentation of monitoring and supervision results; Certification program, the goals of the P5 program were achieved and all parties were satisfied with the existence of the P5 program, which had a positive impact on the students. The P5 program was running well, and all stakeholders were satisfied. However, there was a need for improvement in documentation and communication with students' parents. In addition, it is necessary to broaden project options, support teachers, and encourage them to prioritize character development over tangible results.